PENGARUH SISTEM PENJUALAN ONLINE TERHADAP KEPERCAYAAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN (STUDI PADA PT. WEB WAHANA WISATA) - Aminah Rizkiyah; Budiono Prestyadi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
Consumer Loyality very important means for the company that maintain the sustainability of their business and the continuity of our business activities. Customers faithful consumers is satisfied with products and services provided. Then variable existing as follows: the influence of Online Sales System (X); Customer Trust (Y1); and customer loyalty (Y2);Using the tabulated results of the survey population data on customers of PT Web Wahana Wisata on JL. Veteran 5A Singosari No. 42-Gresik were analyzed using path analysis (path analysis). Then it can be known to the alpha coefficient of each variable in each variable declared reliability because of greater than 0.6. But the value of the hypothesis test is said to be insignificant because the variable does not satisfy the requirements of t-values count > from the t-table, wich is equal to 1,9955 (95%) confidence levels in standart, among other things: the influence of online sales system with customer trust gained by the value t calculate of 0,105. The influence of online sales system with customer loyalty with a value calculate amounted to 1,647. The influence of customer trust and loyalty of customers obtained by values t count of 0,261. But the influence is not direct online sales system of customers loyalty through customer trust gained by the value of 0,00205, which means online sales system that run companies affect customer loyalty.